The role of pre-existing left-sided valvular heart disease in the prognosis of patients with acute myocardial infarction - Muzafarova, Tamilla; Motovska, Zuzana (Frontiers in Cardiovascular Medicine, 2024)
Acute myocardial infarction (AMI) and valvular heart disease (VHD) are the leading causes of cardiovascular morbidity and mortality. The epidemiology of VHD has changed in recent decades with an aging population, increasing risk factors for cardiovascular disease and migration, all of which have a significant implifications for healthcare systems. Due to common pathophysiological mechanisms and risk factors, AMI and VHD often coexist. These patients have more complicated clinical characteristics, in-hospital course and outcomes, and are less likely to receive guideline-directed therapy. Because of the reciprocal negative pathophysiological influence, these patients need to be referred to VHD specialists and further discussed within the Heart team to assess the need for earlier intervention. Since the results of the number of studies show that one third of the patients are referred to the heart teams either too early or too late, there is a need to better define the communication networks between the treating physicians, including internists, general practitioners, outpatient cardiologists and heart teams, after the discharge of patients with pre-existing VHD and AMI.